Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Transmission Dynamics and Immune Responses in a Household of Vaccinated Persons. (17th January 2022) - Liu, Jamin; Laurie, Matthew T; Rubio, Luis; Vazquez, Sara E; Sunshine, Sara; Mitchell, Anthea M; Hapte-Selassie, Matthias; Mann, Sabrina A; Pilarowski, Genay; Black, Douglas; Marquez, Carina; Rojas, Susana; et al.
Abstract: While SARS-CoV-2 vaccines prevent severe disease effectively, postvaccination "breakthrough" COVID-19 infections and transmission among vaccinated individuals remain ongoing concerns. We present an in-depth characterization of transmission and immunity among vaccinated individuals in a household, revealing complex dynamics and unappreciated comorbidities, including autoimmunity to type 1 interferon in the presumptive index case.